Menelusuri Tradisi Tukar Cincin dalam Mappetuada: Implikasi Maqasidh Al-Syariah terhadap Keluarga dan Masyarakat - Jumiyati; Abd. Hakim; Anwar, Wirani Aisiyah; Wahyu, A. Rio Makkulau; Putri Kurniati (Jurusan Hukum Acara Peradilan dan Kekeluargaan, 2024)
This study examines the tradition of exchanging rings in the Mappettuada ceremony, which is part of the engagement process (khitbah) in Bugis culture, with a focus on the implications of Maqasidh al-Syariah for family and society. This tradition not only serves as a symbol of love and commitment between the engaged couple but also reflects the deep social and religious values within Bugis society. The study aims to understand how Mappettuada plays a role in strengthening social bonds and how this tradition aligns with the principles of Maqasidh al-Syariah, particularly in the protection of religion (hifdz al-din), life (hifdz al-nafs), and lineage (hifdz al-nasl). Using a qualitative-descriptive and phenomenological approach, this research explores the dynamics between customary practices and Islamic law in the context of marriage, as well as its impact on family welfare and societal harmony. The findings show that the tradition of exchanging rings in Mappettuada not only strengthens individual and family relationships but also serves as a means to preserve moral and religious values in the Bugis community, demonstrating the synchronization between local customs and Islamic law.